Attitudes To Equality : The "Socialist Legacy" Revisited - Murthi, Mamta, 1965- 1965- (The World Bank, 2008)
It is routinely assumed that residents of post-socialist countries have a preference for greater income equality, other things being equal, owing to the legacy of socialism. This proposition is examined in the context of Eastern Europe and the former Soviet Union using data from three waves of the World Values Survey. Contrary to expectations, the authors find little evidence of a 'socialist legacy' en bloc. Considering the former Soviet Union separately from other post-socialist countries, the analysis finds that as a group these countries display significantly lower preference for moving toward greater income equality than both Eastern Europe and other comparator groups (developed and developing countries). These findings hold up even when controlling for the conventional determinants of attitudes such as income level and employment status of the individual respondent, as well as national factors such as per-capita income and its distribution. Moreover, the preference for greater income inequality appears to have persisted at least since the mid-1990s and possibly since the early 1990s (data difficulties preclude a robust examination of this latter question). The results are consistent with the fairly low levels of public spending on redistribution commonly found in the former Soviet Union